Muscle Oxygenation During Repeated Double-Poling Sprint Exercise in Normobaric Hypoxia and Normoxia - Yamaguchi, Keiichi; Kasai, Nobukazu; Sumi, Daichi; Yatsutani, Haruka; Girard, Olivier; Goto, Kazushige (Frontiers in Physiology, 2019)
We compared upper-limb muscle oxygenation responses during repeated double-poling sprint exercise in normobaric hypoxia and normoxia. Eight male kayakers completed a repeated double-poling sprint exercise (3 × 3 × 20-s maximal sprints, 40-s passive recovery, 5-min rest) in either hypoxia (HYP, FiO2 = 14.5%) or normoxia (NOR, FiO2 = 20.9%). Power output, muscle oxygenation of triceps brachii muscle (using near infrared spectroscopy), arterial oxygen saturation, and cardiorespiratory variables were monitored. Mean power output tended to be lower (-5.2%; P = 0.06) in HYP compared with NOR, while arterial oxygen saturation (82.9 ± 0.9% vs. 90.5 ± 0.8%) and systemic oxygen uptake (1936 ± 140 vs. 2408 ± 83 mL∙min-1) values were lower (P < 0.05). Exercise-induced increases in deoxygenated hemoglobin (241.7 ± 46.9% vs. 175.8 ± 27.2%) and total hemoglobin (138.0 ± 18.1% vs. 112.1 ± 6.7%) were greater in HYP in reference to NOR (P < 0.05). Despite moderate hypoxia exacerbating exercise-induced elevation in blood perfusion of active upper-limb musculature, power output during repeated double-poling exercise only tended to be lower.